Comprehensive investigation into thermal stability of AB-type bio- carbonate hydroxyapatite synthesized via heat-treated bovine bone - Hassanen Jaber; Mohanad H. Mousa; Awais Qadir; Ján Dusza; László Tóth; Péter Pinke; Tünde Kovács (Open Ceramics)
This study investigates the thermal stability and structural changes of AB-type carbonate-hydroxyapatite (AB-type CHA) prepared from heat-treated bovine bone occurring during calcination at 1000, 1100, 1200, and 1300 °C. The structural phase changes and morphological properties of the calcined AB-type CHA samples were assessed by SEM/EDX, XRD, FTIR, and Raman spectroscopy. The findings highlighted that the decomposition of AB-type CHA undergoes three stages: Dehydroxylation, formation of A-type carbonate-hydroxyapatite (A-type CHA), and decomposition. Pure AB-type CHA was stable in a vacuum atmosphere, and no decomposition occurred at temperatures up to 1000 °C. Dehydroxylation and formation of A-type CHA occurred at 1100 °C. The AB-type CHA partially decomposed at a temperature of 1200 °C. A-type CHA, tricalcium phosphate (α-TCP), and tetracalcium phosphate (TTCP) were the main products of the decomposition reactions, and tricalcium phosphate (β-TCP) was also detected in the system. After sintering at 1300 °C, the AB-type CHA was completely decomposed and converted into α-TCP, β-TCP, and TTCP.